Silencing of Decapentaplegic (Dpp) gene inhibited the wing expansion in the white‐backed planthopper, Sogatella furcifera (Horváth) (Hemiptera: Delphacidae). Issue 1 (5th March 2022) - Long, Gui‐Yun; Yang, Jia‐Peng; Jin, Dao‐Chao; Yang, Hong; Zhou, Cao; Wang, Zhao; Yang, Xi‐Bin
Abstract: The Decapentaplegic gene controls wing patterning and spreading by regulating downstream genes in many insect species. However, the molecular characteristics, expression, and biological function of Dpp in Sogatella furcifera remain poorly understood. In this study, we cloned the Dpp gene from S. furcifera and examined its expression levels in different development stages, wing typed adults, and tissues. Then, the function of SfDpp gene was analyzed using an RNA interference (RNAi)‐based approach. The results showed that the full‐length complementary DNA  of the SfDpp gene consists of 1034 bp and contains a 954‐bp open reading frame encoding 317 amino acids. SfDpp has a transforming growth factor‐β (TGF‐β) propeptide superfamily domain and a TGF‐β superfamily domain, typical of members of the TGF‐β superfamily. Quantitative real‐time polymerase chain reaction showed that the expression of SfDpp reached its highest expression level 40 min after eclosion. RNAi‐based gene silencing inhibited transcript levels of the corresponding messenger RNA in S. furcifera nymphs injected with double‐stranded RNA of SfDpp and resulted in death of 29.17% and 26.67% of 4th and 5th instar nymphs, respectively. The wing deformity rate of the adults was 74.12% and 3.41% after SfDpp gene silencing in 4th and 5th instar nymphs, respectively. Examining wing development‐associated genes showed that two target genes of Dpp (Vestigial and Spalt) were both dramatically downregulated after SfDpp was silenced. Our results demonstrate that downregulated SfDpp in early development causes wing expansion failure in S. furcifera . Thus, Dpp may be a target gene for restricting the migration of rice‐damaging planthoppers. Abstract : Caption: SfDpp missing in earlier development stages could lead to S. furcifera wing expansion failure. The messenger RNA expression level of SfDpp were downregulated significantly double‐stranded RNA viruses (dsRNA) in both 4th and 5th instar nymph injected group, but the molting adults of 5th instar nymph injected group expanded their wings entirely while those treated with SfDpp dsRNA failed to expand their wings among the 4th instar injected nymphs. HIGHLIGHTS: The Decapentaplegic (Dpp) gene controls wing development by regulation of downstream genes in many insect species, but its role in regulating wing expansion in the white‐backed planthopper Sogatella furcifera is poorly understood. We characterized the S. furcifera Dpp gene (SfDpp), found it to be a member of the transforming growth factor‐β superfamily, and determined its close evolutionary relationship with the orthologous gene in Nilaparvata lugens and other related species. Knockdown of SfDpp with RNA interference in 4th instar nymphs resulted in a high mortality rate and adult wing deformity among the surviving adults, indicating that Dpp is a target gene that could restrict the migration of rice‐damaging planthoppers.